"You Measure Us and You Depress Us": Healthism and the Subjective Impact of Body Measurements on Secondary School Students. (March 2023) - Beltrán-Carrillo, Vicente J.; Jiménez-Loaisa, Alejandro; González-Cutre, David; Sierra, Ana C.; Valenciano-Valcárcel, Javier
This study explores adolescents' subjective experiences when facing body measurements at school, performed to evaluate the effects of a school-based intervention to promote physical activity. Three semi-structured interviews ( n = 3) and two focus groups ( n = 7 and 3) were conducted with adolescents after measuring some variables related to their weight and adiposity. Observational data ( n = 88) collected by the two researchers in charge of the measurements were also obtained. Findings derived from our thematic analysis question the suitability of body measurements as social contexts where the core ideas of healthism emerge. Some adolescents lived body measurements as negative social experiences, promoting body dissatisfaction, social comparison, embarrassment, and simplistic associations between health and body shape, which could hinder their adherence to healthy habits. We emphasize the role of qualitative research when evaluating pre/posttests of school-based intervention studies, not just the interventions themselves, to generate knowledge to improve research protocols and prevent unwanted psychological outcomes in participants.